Tindak Pidana Sodomi Terhadap Anak - Silangit, H. Nusanatara Tarigan (JUNCTO: Jurnal Ilmiah Hukum, 2024)
This article or paper aims to analyze the factors that cause deviant behavior in the form of sodomy crimes, as well as identify the impact of sexual deviation on victims, especially children. This study uses a normative juridical method with a doctrinal legal approach combined with empirical juridical. The research subjects include secondary legal materials such as laws and regulations, legal doctrines, and related literature, as well as primary data obtained through interviews with law enforcement officials, victims, or victims' families. The instruments used include interview guides, questionnaires, and official documents to support data collection. The results of the study show that sodomy crimes against children are influenced by past trauma factors, socio-economic conditions, environment, and lack of moral values. The impact includes physical injuries, emotional trauma, and severe social stigma for victims. Legal protections such as prevention, therapy, and rehabilitation require the support of family, community, and government. Preventive measures such as early sex education and environmental surveillance are necessary to protect children. A holistic approach is expected to be able to recover victims and prevent similar incidents in the future.